2009
DOI: 10.1111/j.1526-4637.2009.00624.x
|View full text |Cite
|
Sign up to set email alerts
|

Abuse-Related Injury and Symptoms of Posttraumatic Stress Disorder as Mechanisms of Chronic Pain in Survivors of Intimate Partner Violence

Abstract: Management of chronic pain in IPV survivors requires attention to symptoms of PTSD, abuse-related injury, and lifetime experiences of violence. Ensuring that acute pain from injury is adequately treated and followed over time may reduce the extent of chronic pain in abused women. The results also support the importance of routine assessment for IPV and child abuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
2
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 46 publications
2
53
2
6
Order By: Relevance
“…In an earlier analysis, we found that PTSD symptom severity and lifetime abuse-related injury were each significant mediators of the relationships between both assaultive IPV and child abuse severity and chronic pain severity in women survivors of IPV. 24 Depressive symptoms may also be an important link between lifetime trauma and physical health outcomes. 25 In meta-analyses, depression has been estimated to affect as many as 47.6% of abused women 21 and to be moderately associated with physical partner assault.…”
Section: Introductionmentioning
confidence: 99%
“…In an earlier analysis, we found that PTSD symptom severity and lifetime abuse-related injury were each significant mediators of the relationships between both assaultive IPV and child abuse severity and chronic pain severity in women survivors of IPV. 24 Depressive symptoms may also be an important link between lifetime trauma and physical health outcomes. 25 In meta-analyses, depression has been estimated to affect as many as 47.6% of abused women 21 and to be moderately associated with physical partner assault.…”
Section: Introductionmentioning
confidence: 99%
“…8,37 Chronic pain frequently occurs in the absence of injury and may be associated with trauma through prolonged stress responses, causing pathological changes in stress responses, such as allostatic load. 38 The self-medication hypothesis posits that some individuals use substances to alleviate negative affect and physical discomfort. 39−42 Thus, it is not surprising that women with interpersonal victimization are more likely to receive prescriptions for psychotherapeutic drugs, including sedatives, anxiolytics, and painkillers, then women without partner violence.…”
Section: Introductionmentioning
confidence: 99%
“…The conjugal context of violence in which some women find themselves increases their risk of developing various physical and mental health problems as well as social functioning and parenting problems [42][43][44][45]. Moreover, these women often find themselves isolated or forced to take time off from work due to difficulties at home [44].…”
Section: Direction Of Violence and Impact On Parental Rolesmentioning
confidence: 99%